2021
DOI: 10.1016/j.resconrec.2020.105171
|View full text |Cite
|
Sign up to set email alerts
|

Using hybrid choice models to capture the impact of attitudes on residential greywater reuse preferences

Abstract: This is a repository copy of Using hybrid choice models to capture the impact of attitudes on residential greywater reuse preferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
(75 reference statements)
1
9
0
Order By: Relevance
“…The highest female concentration is in Class 2 and the highest male concentration is in Class 1. This indicates a more negative view of GWR by women than by men, which is in agreement with results obtained in other studies (Amaris et al, 2021;Wester et al, 2015), which have been linked to the higher susceptibility of women to associate reuse with high levels of risks (Mankad & Tapsuwan, 2011). However, it is important to highlight that other studies have also found the opposite effect or no relation between gender and water reuse acceptability (Garcia-Cuerva et al, 2016;Mason et al, 2018).…”
Section: Posterior Values Of Socioeconomic Characteristics Across Cla...supporting
confidence: 91%
See 2 more Smart Citations
“…The highest female concentration is in Class 2 and the highest male concentration is in Class 1. This indicates a more negative view of GWR by women than by men, which is in agreement with results obtained in other studies (Amaris et al, 2021;Wester et al, 2015), which have been linked to the higher susceptibility of women to associate reuse with high levels of risks (Mankad & Tapsuwan, 2011). However, it is important to highlight that other studies have also found the opposite effect or no relation between gender and water reuse acceptability (Garcia-Cuerva et al, 2016;Mason et al, 2018).…”
Section: Posterior Values Of Socioeconomic Characteristics Across Cla...supporting
confidence: 91%
“…To ensure that laws, regulations, and policies contribute to making these systems more attractive and to remain successful over time, an understanding of the key determinants of consumer preferences is essential (Mukherjee & Jensen, 2020). Several studies on water reuse have empirically demonstrated that there is heterogeneity in preferences and that this is mainly linked to socio-demographic characteristics, and other psychological constructs (Amaris et al, 2021;Oteng-Peprah et al, 2020). The starting point of our work is that even within the same sociodemographic group, differences in preferences may exist, in terms of which (if any) uses of greywater are desirable, and what the role of the appearance of the water is (Amaris et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HC model with latent variables used in this paper was estimated previously by (Amaris et al, 2021b) for the city of Santiago. This type of model incorporates a role for additional psychometric constructs, in this case an attitude towards greywater reuse, which was calibrated using the six attitudinal statements described in section 3.2.…”
Section: Hybrid Choice (Hc) Model With Latent Variablesmentioning
confidence: 99%
“…The first, reported in Amaris et al (2021a), is a latent class (LC) model used to identify segments in the population with different behaviour/preferences according to their sensitivities to changes in the greywater service. The second, reported in Amaris et al (2021b), is a hybrid choice (HC) model used to capture the heterogeneity in preferences, based on individual characteristics and psychological constructs towards greywater. It is important to highlight that much of the work in this area makes use of experimental techniques rather than "real world" decisions, especially for choices involving new products and/or services.…”
Section: Introductionmentioning
confidence: 99%